The state of the art of extracellular vesicle research in protozoan infection - Wang, Xinlei; Chen, Jie; Zheng, Jingtong (Frontiers in Genetics, 2022)
Protozoan diseases seriously affect the health of human beings, livestock and poultry and lead to high economic and medical costs. Extracellular vesicles (EVs) are membranous structures formed through biological processes that play important roles in immune regulation. Studies have shown that parasites transmit information to hosts through EVs to modulate host immune responses. The major roles played by EVs released from parasites involve facilitating parasitization of the host. In this review, we discuss relevant recently obtained data on EVs secreted by different kinds of protozoa, including their molecular mechanisms, and discuss the roles played by EVs in the occurrence and development of parasitic diseases.